Emerging directions in doctoral education - Blessinger, Patrick; Stockley, Denise (Bingley, U.K. : Emerald, 2016)
This volume examines how universities and colleges around the world are developing innovative ways to provide doctoral education, including new theories and models of doctoral education and the impact of changes in government and/or accreditation policy on practices in doctoral education.
This volume examines how universities and colleges around the world are developing innovative ways to provide doctoral education, including new theories and models of doctoral education and the impact of changes in government and/or accreditation policy on practices in doctoral education. Specifically, this volume looks at the emerging trends in student selection practices, research topic selection, supervision practices, and dissertation review and approval process across a range of disciplines across different institutional types across different countries. Seeking to understand the current landscape of how universities are preparing the next generation of researchers, scholars, scientists, and university faculty, Emerging Directions in Doctoral Education is a must-read for faculty, researchers, accreditation agencies, doctoral students and policymakers.
Innovative approaches in doctoral education: an introduction to emerging directions in doctoral education / Patrick Blessinger, Denise Stockley -- Doctoral education for the future: through the looking glass / Gerard Hoyne, Julia Alessandrini, Marc Fellman -- Scholar-in-training; Leader-in-training: the Rutgers University Predoctoral Leadership Development Institute / Ralph A. Gigliotti, Brian D. Agnew, Christine Goldthwaite, Surabhi Sahay, Maria Dwyer, Brent D. Ruben -- Managing the psychological contract within doctoral supervisory relationships / Sally Sambrook -- Disciplinarity issues in educational technology doctoral supervision / Gale Parchoma, Jeffrey M. Keefer -- Living theory in action: preparing a new generation of educational researchers / Karen L. Ford, Elena Yu. Polush, Nancy J. Brooks -- Creating a decolonized alliance: American Indian and Alaska native doctoral leadership program / Kem M.Gambrell, Lazarina N.Topuzova -- Collision and coalescence - German and British cultures in doctoral education / Wolfgang Deicke, Johannes Moes, Johannes Siemens -- Client-based dissertations in practice / Kathleen Haywood, Kimberly Allen, Felicita Myers -- Learning like adults: a hybrid interdisciplinary doctoral program for mid-career professionals / Judith Beth Cohen, Jo Ann Gammel, Amy Rutstein-Riley -- Applying self-determination theory to improve completion rates in a part-time professional doctorate program / Grace McCarthy -- Differentiation and integration: managing the paradox in doctoral education / Jon F.Wergin, Laurien Alexandre -- Qualified ... for what? the potential for qualifying exams to become meaningful professional milestones / Jessica Riviere -- Joint doctoral supervision across countries: changes, challenges and considerations / Elise van den Hoven, Julia Connell -- Developing institutional leadership for the scholarship of graduate student supervision: lessons learned in a Canadian research-intensive university / Anthony Clarke, Harry Hubball, Andrea Webb.
Includes bibliographical references.
Print version record
Keywords: Education -- Higher; Universities; Universities and colleges -- Graduate work; Doctoral students -- Education